PAINT YOURSELF POSITIVE : Colourful, creative watercolour - Haines, Jean (Tunbridge Wells, Kent : Search Press, 2019)
Follow renowned author and artist Jean Haines as she leads you on an exciting journey through paint; showing you how to overcome challenges and find a new outlook with each stroke of watercolour paint.
Includes index
Keywords: Watercolor painting